PEMBARUAN SISTEM PERADILAN PIDANA ANAK YANG BERKEADILAN RESTORATIVE (Suatu Analisa Yuridis Penyelesaian Penanganan Perkara Tindak Pidana Asusila Anak Berkonflik Dengan Hukum dengan Korban Anak di Bawah Umur) - Endang Sri Lestari; Ahmad Muchlis (Universitas Muhammadiyah Jember, 2020)
Children as the next generation of the nation become the hope of Indonesia's development in the future. Of course, when children face legal problems, they are entitled to get legal protection in order to achieve a sense of justice itself. In reality, children who are dealing with the law, both their capacity as perpetrators and victims are very vulnerable and so easily become victims of legal injustice. There are factors that must be considered in the process of law enforcement in order to achieve a sense of justice, including by choosing the right punishment for the child. Diversity and the concept of restorative justice need to be taken into consideration in handling cases of children who commit criminal acts of child protection.This writing is a normative study, then analyzed qualitatively by descriptive methods. Based on the results of the discussion and analysis, it is concluded that the diversion stages and the concept of restorative justice are needed as a consideration for judges to impose their convictions.